Carbon-slurry optimization for lithium-ion batteries customization (2023)
ABSTRACT: The technological application of lithium-ion batteries (LIB) grows constantly, making customization of the batteries a current necessity and sometimes a challenge. In this paper we described carbon-slurry optimization process for anodes of lithium-ion batteries customization by using a surface response statistical experiment with four response variables such specific discharge capacity, coulombic efficiency, anodes mass deviation, and capacity retention. We studied two commercial graphite active materials by characterizing the materials via Raman spectroscopy, SEM, and electrochemical techniques. We corroborate the graphite structure for both materials but with morphological differences such as shape and particle size. The binder composition seems to interfere with the active carbon materials capabilities while it generates better performance for one of them. Although the chemical structure of both materials was confirmed to be the same via Raman experiments, SEM images shows critical morphological differences that interferes with the final slurry thus, affecting the electrochemical performance of the anodes. Further studies are required to understand ECSA and its possible effect on the charge/ discharge capacities of the anodes.